IMPROVING THE EMPLOYEE MOTIVATION SYSTEM IN HEALTHCARE ORGANIZATIONS - Mirdadayeva Dilfuza Davlatovna; Sattarova Zebo Rasulovna (Journal Park Publishing, 2025)
Effective employee motivation is a critical factor influencing the quality, efficiency, and sustainability of healthcare services. In medical organizations, staff performance is closely linked to professional satisfaction, organizational commitment, and the ability to deliver high-quality patient care. However, healthcare workers often face high workloads, emotional stress, and limited career advancement opportunities, which can reduce motivation and negatively affect organizational outcomes. This article aims to analyze approaches to improving the employee motivation system in healthcare organizations. Both financial and non-financial incentive mechanisms are examined, including remuneration policies, performance-based rewards, professional development opportunities, recognition systems, and supportive work environments. Particular attention is given to the role of organizational culture, leadership, and management practices in enhancing staff engagement and job satisfaction. Strengthening motivation systems in healthcare organizations may contribute to improved workforce retention, increased service quality, and better overall healthcare performance.
Keywords: Healthcare organization, employee motivation, incentive system, job satisfaction, human resource management, healthcare workforce.